Editorial - Jesús García-Laborda; Slavka Madarova (Universidad Nacional de Colombia, 2017)
Journals tend to be regional in the sense that their readership usually focuses on its own personal scope. For instance, it is hard to find a truly international journal with papers from many different countries. However, this time Profile journal has made a major effort to obtain valuable contributions from beyond the South American continent. In fact, this special issue brings together a number of very appealing topics which reflect on a common tendency. There is a clear orientation towards technology-based language teaching which can be seen in many parts of the world.